2010
DOI: 10.1111/j.1349-7006.2010.01504.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel combination treatment for colorectal cancer using Nek2 siRNA and cisplatin

Abstract: Nek2 (NIMA-related kinase 2) is involved in cell division and mitotic regulation by centrosome splitting. We previously reported that Nek2 depletion causes growth suppression and cell death in cholangiocarcinoma and breast cancer cells. In this report, we examine the effect of a combination treatment using Nek2 siRNA with the cytotoxic chemotherapeutic agent cisplatin (CDDP) on colorectal cancer. Nek2 was overexpressed in all colorectal cancer cell lines examined (HCT-15, DLD-1, Colo205, and Colo320). Nek2 sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 46 publications
6
64
0
1
Order By: Relevance
“…Several kinases that had been previously shown to regulate telomerase were also among the hits, confirming the specificity of the functional read-out of the HTS (6)(7)(8). Moreover several of the identified kinases have been found overexpressed in different human cancers and are now being exploited as potential targets for cancer therapeutics (20)(21)(22)(25)(26)(27)(28)(29). Subsequent validation experiments showed that modulation of some of these proteins resulted in perturbation of telomerase function and elicited phenotypic changes characteristic of telomere dysfunctions, suggesting that the proteins identified in our screen are likely true modifiers of telomerase.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Several kinases that had been previously shown to regulate telomerase were also among the hits, confirming the specificity of the functional read-out of the HTS (6)(7)(8). Moreover several of the identified kinases have been found overexpressed in different human cancers and are now being exploited as potential targets for cancer therapeutics (20)(21)(22)(25)(26)(27)(28)(29). Subsequent validation experiments showed that modulation of some of these proteins resulted in perturbation of telomerase function and elicited phenotypic changes characteristic of telomere dysfunctions, suggesting that the proteins identified in our screen are likely true modifiers of telomerase.…”
Section: Discussionmentioning
confidence: 73%
“…There is now substantial evidence that NEK2, NEK6, NEK7, and NEK9 regulate mitotic progression and mitotic spindle organization (24). Furthermore, high expression levels of NEK kinases have also been found in human cancers, such as breast and bladder cancers (25,26) and NEK kinases are now being pursued as potential therapeutic targets (27,28). Members of the MAPK superfamily were also selected given their diverse functions in a wide variety of biological processes (9,29).…”
Section: Resultsmentioning
confidence: 99%
“…Several data sets have also indicated that NEK2 is up-regulated in breast tumors expressing mutant p53 compared with WT. This is of particular importance because NEK2-based anticancer therapies are under preclinical development (42,43). If NEK2 protein is similarly up-regulated in mutant p53-expressing tumors, then these patients may achieve better benefits from NEK2-based therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the relationship between NEK2 and drug resistance is unclear, with only several studies indicating its drug resistance-related functions. The combined use of both NEK2 siRNA and cisplatin inhibited cell proliferation and induced apoptotic cell death in vitro, suggesting that NEK2 may be associated with drug resistance in colorectal cancer (38). Similarly, the combination of NEK2 siRNA with paclitaxel and doxorubicin was found to improve the sensitivity of breast cancer cells during chemotherapy treatment (20).…”
Section: Function Of Nek2 In Cancersmentioning
confidence: 99%